INDONESIAN FREE ACTIVE POLITICS AND CHALLENGES IN DEFENSE BUDGET LIMITATIONS - Bambang Aziz Pamungkas Wardhana; Muradi .; Wawan Budi Darmawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2021)
This paper discusses the impact of the adoption of a free and active policy by Indonesia on the huge budget requirement for the development of Indonesia's defense forces. The use of a free and active foreign policy means that Indonesia will not be involved in any form of military alliance. Thus, Indonesia must increase its military strength optimally and maximally, of course with the support of a very large budget. In this paper, the author uses qualitative research methods. In this study, several things were found, among others, in meeting the creation of the MEF, the defense budget allocation from GDP was at least 2%, while until now the defense budget allocation compared to GDP is still less than 1%. The non-fulfillment of the defense budget has an impact on the non-realization of the MEF since it was enacted. In the end, this paper concludes that the problem of limited defense budget experienced by Indonesia is an impact of the adoption of free and active politics.